Controlling environmental policy : the limits of public law in Germany and the United States - Rose-Ackerman, Susan (Yale University Press, 1995)
"Although many people feel that Germany provides a model for environmental policymaking, this book shows that it does not. German administrative law, which focuses on individuals' complaints against the state for violating their rights, does not deal adequately with the broad issues of democratic legitimacy and accountable procedures raised in American courts. Susan Rose-Ackerman compares regulatory law and policy in the United States and Germany and argues that the American system can provide lessons for those seeking to reform environmental policymaking in Germany and the newly democratic states of eastern Europe." "Democratic governments, says Rose-Ackerman, face the problem of balancing the desires and expertise of conflicting interest groups, such as those that concern themselves with environmental protection. Under German law, however, environmental associations with policy agendas have no enforceable legal right to participate in federal policymaking, and regulation writing is much less open and accountable than in the United States. The U.S. Supreme Court is moving in the direction of the German system - away from review of the rulemaking process and toward a focus on individual rights. Those who support this trend should look critically at the German solution."--Jacket